The Government Expenditures, Economic Growth and Poverty Levels in Nigeria: A Disaggregated Approach - Emmanuel Agbeni, Kehinde; Akanni, Olusola; Yetunde Francisca , Adekoya; Judith Gbadebo, Adedoyin; Chioma Ejikeme , Precious; Alexander Nwuko, Obinna; Ezeokolie, Chima (SMARTINDO, 2025)
Purpose - This study uses the disaggregation approach to investigate how government spending affects economic growth and poverty levels in Nigeria. The study was anchored on the human capacity theory and two specific objectives were formulated to guide the study. Recent estimates indicate that 67.12% of the Nigerian population is living below one dollar per day. Nationally, 40.7 percent of Nigerians (89 million people) live below the poverty line, while another 25 percent (53 million) are vulnerable (World Bank,2024). Design/methodology/approach - This study using secondary data, this study looks at how different sectors of government expenditures affected poverty and economic growth in Nigeria between 1991 and 2023. Short- and long-run relationships are evaluated using the Autoregressive Distributed Lag (ARDL) model, and nonlinear effects are examined using the Threshold Regression Approach. To determine the direction of causality, the study also employs the Granger Causality Test and the Error Correction Model. Originality - The authors here by declare that no generative AI tools, including text-to-image generators and large language models (ChatGPT, COPILOT, etc.), were used in the creation or editing of manuscripts. Findings and Discussion - reveal that while economic growth insignificantly reduces poverty in both the short and long run, government spending does not have a statistically significant impact on poverty in Nigeria. In the short run, recurrent expenditures on agriculture, health, and education negatively but insignificantly affect economic growth, while expenditures on debt servicing and road construction show a negligible positive effect. Poverty will decrease by 0.45 points in the short term and 0.96 points in the long term for every point increase in government spending at the 1% level of significance. The findings did not support the Keynesian theory or Wagner's Law in Nigeria, which found that government spending increases economic growth and it has ability in reducing poverty in an economy. The study concludes that the current economic trajectory in Nigeria cannot be sustained and recommends increased government allocations to priority sectors such as health, education, agriculture, and infrastructure. Conclusion - Based on this finding, we can conclude that the type of government expenditure in Nigeria sectors on (Education, Agriculture and Health) have either been insufficient or have not been effectively and efficiently allocated as its ability to reduce poverty is very low and insignificant. It concludes that the current economic trajectory cannot be sustained and recommends increased government allocations to priority sectors such as health, education, agriculture, and infrastructure.